Majlis Perbandaran Jempol / Nur Syuhaida Shuhaiman - Shuhaiman, Nur Syuhaida (Faculty of Business and Management, 2023)
For students in their last year of study at their individual institutions, the internship program is a requirement. Additionally, it serves as a platform for students to see firsthand the realities of the workplace. Additionally, it is to obtain experience in the actual work processes or working settings that they may require in the future. Students can profit from this practical program's experience by developing a professional attitude towards work and knowledge of the workplace they will encounter in the future. They can learn how to interact with individuals based on their circumstances. As a result, it can increase their maturity of thinking and also their action towards that. Jempol Municipal Council (MPJL) was the starting point of my wonderful six-month industrial training, during which I gained a lot of knowledge and experiences. Jempol Municipal Council (MPJL) is a government body whose function is as a development center and also provides comfortable services to the residents of the Jempol area. It is under recognized local authority (PBT). This means that it is under the supervision of the Negeri Sembilan Government. The essence of the content that needs to be in this internship report is quite a lot and it is divided into many parts and starts by introducing the company profile. The following section is a reflection on the industrial training, and it discusses the knowledge and expertise gained during the training and applied. The main conclusions of the report are based on a SWOT analysis of the company's strengths, weaknesses, opportunities and threats. Discussions and advice on company SWOT analysis are provided in this area. After analyzing the swot for the Jempol Municipal Council, I finally managed to identify what this company's swot is. For Strength, it must be due to Well-known recognized local authority (PBT) and good working environment or condition. For weaknesses, Non-Technology Updated and Lack of job opportunities for high level positions such as officers. For opportunities, it is a surplus in the budget for allocation and also has a strategic local area. Lastly, for threat is economic crisis and also change the government.